2018
DOI: 10.1038/sdata.2018.173
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging and clinical data archive for head and neck squamous cell carcinoma patients treated with radiotherapy

Abstract: Cross sectional imaging is essential for the patient-specific planning and delivery of radiotherapy, a primary determinant of head and neck cancer outcomes. Due to challenges ensuring data quality and patient de-identification, publicly available datasets including diagnostic and radiation treatment planning imaging are scarce. In this data descriptor, we detail the collection and processing of computed tomography based imaging in 215 patients with head and neck squamous cell carcinoma that were treated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 21 publications
0
59
0
1
Order By: Relevance
“…org/10.7937/K9/TCIA.2015.7AKGJUPZ), 22,30,46,60,66 Head-Neck-PET-CT (https://doi.org/10.7937/K9/TCIA.2017.8oje 5q00), 22,30,46,114 TCGA-HNSC (https://doi.org/10.7937/K9/ TCIA.2016.LXKQ47MS) 22,60 and Data from Head and Neck Cancer CT Atlas (https://doi.org/10.7937/K9/TCIA.2017. umz8dv6s) 22,115 CT image databases, the RT-MAC (https://d oi.org/10.7937/tcia.2019.bcfjqfqb) 116 MR image database, or TABLE I. Image modalities used for auto-segmentation of organs at risk in the head and neck region for the purpose of radiotherapy planning, and the corresponding references.…”
Section: C Image Databasementioning
confidence: 99%
“…org/10.7937/K9/TCIA.2015.7AKGJUPZ), 22,30,46,60,66 Head-Neck-PET-CT (https://doi.org/10.7937/K9/TCIA.2017.8oje 5q00), 22,30,46,114 TCGA-HNSC (https://doi.org/10.7937/K9/ TCIA.2016.LXKQ47MS) 22,60 and Data from Head and Neck Cancer CT Atlas (https://doi.org/10.7937/K9/TCIA.2017. umz8dv6s) 22,115 CT image databases, the RT-MAC (https://d oi.org/10.7937/tcia.2019.bcfjqfqb) 116 MR image database, or TABLE I. Image modalities used for auto-segmentation of organs at risk in the head and neck region for the purpose of radiotherapy planning, and the corresponding references.…”
Section: C Image Databasementioning
confidence: 99%
“…We retrospectively acquired clinical and imaging data from (1) Yale's Smilow Hospital cancer registry from 2009-2019, and (2) two publicly available TCIA collections [36]: the "Head-Neck-PET-CT" collection from four Canadian institutions ("Canadian" cohort) [37,38] and the "Data from Head and Neck Cancer CT Atlas" collection from MD Anderson Cancer Center ("MD Anderson" cohort) [39,40]. Institutional review board approval was obtained from the Yale University ethics committee (IRB protocol #2000024295) and informed consent was waived, given the retrospective study design.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…We analyzed PET images and patient data from Xiamen, China and Charité Berlin, Germany plus additional images and patient data from three American databases, available in the cancer imaging archive [11][12][13][14]. Data for the Chinese patients and the patients of the cancer imaging archive have been published previously [15][16][17][18].…”
Section: Patientsmentioning
confidence: 99%
“…Several publications suggest that 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) parameters bear prognostic value in NPC and could potentially be used for treatment individualization. Two meta-analyses investigated the prognostic role of FDG-PET in NPC and found that the parameters maximum standardized uptake value (SUV max ), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) bear a significant prognostic value for various important clinical endpoints, including event-free survival (EFS) and overall survival (OS) [4,5].…”
Section: Introductionmentioning
confidence: 99%